2015
DOI: 10.1093/jac/dkv014
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nephrotoxicity onset associated with polymyxin B therapy

Abstract: Risk factors for nephrotoxicity onset associated with polymyxin B were identified. In conjunction with susceptibility and other pharmacokinetic/pharmacodynamic data, our results can be used to optimize treatment for MDR Gram-negative infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 20 publications
4
38
3
4
Order By: Relevance
“…CMS or PMB occurred 2 days after initiation of therapy, with the majority of cases occurring after 15 days of therapy [46]. Fortunately, polymyxin-associated nephrotoxicity was, however, reversible in most patients [47,50]. …”
Section: Toxicodynamics Of Polymyxinsmentioning
confidence: 99%
“…CMS or PMB occurred 2 days after initiation of therapy, with the majority of cases occurring after 15 days of therapy [46]. Fortunately, polymyxin-associated nephrotoxicity was, however, reversible in most patients [47,50]. …”
Section: Toxicodynamics Of Polymyxinsmentioning
confidence: 99%
“…So, use of these alternate body size descriptors limits computation of doses that may be erroneously high. A good example for this potential error is with the antimicrobial Polymyxin B, which has a high incidence of nephrotoxicity [27][28][29][30][31]. For safety, dosage of this antimicrobial on IBW should lead to computation of smaller doses compared to TBW-based doses across the clinical population [31].…”
Section: Obesity and Initial Dose Selection Approachesmentioning
confidence: 99%
“…However, pharmacokinetic studies have reported preferential accumulation and prolonged residence of polymyxin B in rat kidneys (7,8). Several studies have also reported a daily dose of polymyxin B as an independent risk factor associated with drug nephrotoxicity (9)(10)(11). Nevertheless, these reports did not provide a mechanistic framework correlating renal drug exposure with the onset of polymyxin B nephrotoxicity.…”
mentioning
confidence: 99%